The role of intestinal microbiota in the pathogenesis of colorectal carcinoma - Kuzma, Jozef; Chmelař, Dittmar; Hájek, Michal; Lochmanová, Alexandra; Čižnár, Ivan; Rozložník, Miroslav; Klugar, Miloslav (Folia microbiologica, 2020)
The symbiotic relationship between intestinal microbiota and the host is a major mechanism of prevention against the development of chronic and metabolic diseases. The intestinal microbiota provides several physiological functions of the organism from the creation of a natural functional barrier with a subsequent immunostimulatory activity up to affecting the energy metabolism of the host. Disruption of physiological intestinal microbiota is reported as one of the major etiological factors of initiation and progression of colorectal carcinoma (CRC). Chronic low-grade inflammation is associated with the development of CRC, through the production of inflammatory cytokines and reactive oxygen species. CRC occurs in association with high-protein and high-fat diets in combination with low-fiber intake. The problem of intestinal dysbiosis and oncological diseases is a multidisciplinary problem and it is necessary to focus on several fields of medicine such as public health, clinical pharmacology, and internal medicine. The aim of this review is describing the role of gut dysbiosis in pathogenesis of colorectal carcinoma.
Keywords: gastrointestinální trakt; Symbiosis; dysbióza; dieta; Inflammation; střevní mikroflóra; kolorektální nádory; Dysbiosis; reaktivní formy kyslíku; cytokiny; zánět; Colorectal Neoplasms; Gastrointestinal Tract; Cytokines; Gastrointestinal Microbiome; Reactive Oxygen Species; Humans; symbióza; Diet; lidé